Effect of Breastfeeding on Relieving Pain during Immunization in Infant - Bhurtel, R.; Yadav, U.; Chaudhary, R.; Shah, S.; Poudel, P.; Pokhrel, R. P.; Sharma, S. (Kathmandu University Medical Journal, 2020)
Background Advantages due to immunization are numerous and cannot be avoided but at the same time pain inflicted on babies needs to be addressed when possible. Pain associated with immunization injections has often been overlooked when remedies are available. Objective To find out the effect of breastfeeding on relieving pain during immunization injection in infants. Method An experimental study was conducted at Immunization clinic of B.P. Koirala Institute of Health Sciences (BPKIHS). Total 124 subjects were divided randomly into two groups. Experimental subjects were allowed to breastfeed for 5-10 minutes before immunization while control group was immunized without breastfeeding. Interview Questionnaire was used to obtain demographic variables and measurements were obtained. Measures of pain was recorded using duration of cry and Modified Behavior Pain Scale, by Taddio et al. Data was analyzed by using SPSS 20.0 where variables were assessed with frequency tables, Pearson’s Chi-Square test, independent t test and Mann Whitney U test. Result The mean pain score in experimental group was 7.10 and in control group 7.56 which was statistically significant (p=0.001). The median duration of cry was significantly shorter in experimental group i.e. 25 seconds (IQR: 20-30) than control group 42.5 seconds (IQR: 30-61.5) (p < 0.001). Conclusion Breastfeeding before immunization is effective in reducing pain in infants.